Development of a duplex rapid assay for immunoglobulins M and G to evaluate the parvoviral immune status of clinically healthy dogs. (May 2016) - Palma, Marco; de la Roja, Nuria; Montón, Mercedes; Sastre, Patricia; Ramírez, Susana; Barreiro, Belén; Venteo, Angel; Rueda, Paloma
A duplex rapid assay for detection of serum antibodies to canine parvovirus (CPV) was developed. Canine immunoglobulin (Ig)M or IgG were captured in immunotubes with anti-canine IgM or IgG and detected with parvovirus VP2 recombinant protein followed by an anti-VP2 monoclonal antibody. The assay was tested using a collection of sera from dogs that were vaccinated against CPV on arrival at an animal shelter in Madrid, Spain. Results were compared with those of 2 commercial enzyme-linked immunosorbent assays (ELISAs) considered as reference techniques. A high correlation was found between the duplex rapid assay and the ELISAs, presenting an accuracy of 98% and 100% for IgG and IgM, respectively. According to the IgG and IgM levels at days 0–3 postvaccination, the samples were divided into 2 groups. One group of dogs showed high IgG and low IgM values at the first sampling post-vaccination and during the following 14 days, indicating that they had previously been in contact with the virus, either by vaccination or infection before arrival at the animal shelter. A second group of dogs appeared to be unvaccinated or uninfected before arrival at the animal shelter because they had negative IgM and IgG values soon after vaccination. These animals responded to vaccination, as demonstrated by seroconversion of both isotypes of immunoglobulins. The developed assay appears to be useful in determining the unknown immune status of dogs to CPV, especially in kennels and shelters where the rate of infection by CPV is relatively high.